2007
DOI: 10.1080/13691180701658095
|View full text |Cite
|
Sign up to set email alerts
|

Networked Individualism of Urban Residents: Discovering the communicative ecology in inner-city apartment buildings

Abstract: URBAN RESIDENTSDiscovering the communicative ecology in inner-city apartment buildings Certain patterns of interaction between people point to networks as an adequate conceptual model to characterize some aspects of social relationships mediated or facilitated by information and communication technology. Wellman proposes a shift from groups to networks and describes the ambivalent nature inherent in an egocentric yet still well-connected portfolio of sociability with the term 'networked individualism'. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4
2

Relationship

3
7

Authors

Journals

citations
Cited by 133 publications
(83 citation statements)
references
References 26 publications
2
81
0
Order By: Relevance
“…We join other recent HCI papers to explore communicative ecologies and repertoires in resource constrained settings [34,35]. Communicative ecologies involve interactions among technologies, sociality, and discourse [36,37]. Information or cultural ecologies are characterized by 'hybrid' interactions of physical and digital [8,38].…”
Section: Framing/perspectivementioning
confidence: 99%
“…We join other recent HCI papers to explore communicative ecologies and repertoires in resource constrained settings [34,35]. Communicative ecologies involve interactions among technologies, sociality, and discourse [36,37]. Information or cultural ecologies are characterized by 'hybrid' interactions of physical and digital [8,38].…”
Section: Framing/perspectivementioning
confidence: 99%
“…Residents of local communities rely on many systems to communicate and propagate information [14]. Traditional media, internet-enabled systems and word of mouth comprise the communicative ecology of a neighborhood.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research found that -despite not knowing many of their neighbours -urban residents believe that it is very likely that within the diversity of residents living in the same neighbourhood, there may be some who they might be socially compatible with, alas certainly not all of them [8]. Yet, apart from serendipitous encounters, there are no convenient means to find out if they are.…”
Section: Collective Vs Network Socialitymentioning
confidence: 99%